Hubungan Pola Asuh Demokratis Dan Kecerdasan Emosi Dengan Perilaku Prososial Pada Remaja - Kurniawati Husada, Anna (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2013)
Abstract. This study aims to examine the relationship of democratic parenting style and emotional intelligence and pro social behaviors in adolescents, especially in Cita Hati junior high school Surabaya. Sampling technique in this study is a simple proportional random sampling technique. Researchers determined by drawing samples taken 2 classes at each level (2 classes of grade 7 and 2 classes of grade 8) and obtained the number of students 96. Based on the regression analysis using SPSS 20, it is found F = 111.993 at p = 0.000 (p <0,01). It can be concluded that the variables jointly democratic parenting style and emotional intelligence significantly correlated with pro social behavior variable. Effective contribution of these two variables X to Y is shown on the price of R2 = 0.707, which means democratic parenting variables and emotional intelligence together an impact of 70.7% on pro social behavior. Partially, the result of statistical calculations showed prices at t = 5.965 p = 0.000 (p <0.05) for the correlation between democratic parenting variables with pro social behavior. Price at t = 2.961 p = 0.008 (p <0.05) for the correlation between emotional intelligence variables with pro social behavior, that is to say, in partial democratic parenting emotional intelligence variables correlated and also correlated significantly with pro social behavior. Keywords: Democratic Parenting, Emotional Intelligence, Pro social Behavior.